Idiopathic pulmonary fibrosis : a comprehensive clinical guide - Nathan, Steven D.; Meyer, Keith C. (Respiratory Medicine, 2014)
Idiopathic Pulmonary Fibrosis: A Comprehensive Clinical Guide delivers a concise review of our current understanding of disease pathogenesis and provides current evidence in the medical literature regarding its diagnosis and management.  Each chapter  includes key points and a summary aiming to update clinicians about various issues concerning the diagnosis and management of IPF. In addition to outlining the current state of knowledge, each chapter  also provides a summary of ongoing research and identifies the needs for future research in the field.  Idiopathic Pulmonary Fibrosis: A Comprehensive Clinical Guide is an important new text that provides its readers with a better understanding of the pathobiology and natural history of IPF as it continues to evolve.